TRANSFORMATION OF MSME’s COFFEE SHOPS IN MEDAN CITY: THE ROLE OF SUPPLY CHAINS AND BUSINESS INNOVATION IN IMPROVING COMPETITIVENESS THROUGH ENTERPRENEURIAL COMPETENCE AS A CATALYST - Syukron Arjuna; Munthe Abdillah; Yasir Pohan (CV. Radja Publika, 2026)
The coffee shop business is growing rapidly, with many entrepreneurs facing problems in maintaining the sustainability of their businesses. Some of the main problems that often arise include limitations in financial management, a lack of innovation in products and services, and problems in the supply chain for quality coffee beans. The purpose of this study is to determine the direct and indirect effects of supply chains and business innovation on competitiveness through entrepreneurial competence. This type of research is associative research. The types of data used are primary data and secondary data obtained from interview questionnaires and documentation studies. The population in this study is all coffee shop MSMEs in Medan City, the number of which cannot be determined with certainty. Accidental sampling was used. Based on the Lameshow formula, the sample size is 100 respondents, but the researcher added 50 respondents so that the total sample became 150 respondents in order to make the results more representative and avoid data bias. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that supply chains directly do not have a significant effect on entrepreneurial competence, business innovation directly has a significant effect on entrepreneurial competence, supply chains directly have a significant effect on competitiveness, business innovation directly has a significant effect on competitiveness, and business innovation directly has a significant effect on competitiveness. Supply chains and business innovation indirectly have a significant effect on competitiveness through entrepreneurial competence.